The Actualization of Social Care Characters in Academic Society in Responding to the Covid-19 Pandemic - Krisna Dwiputra, Dimas Febriansyah; Sundawa, Dadang; Iqbal, Muhamad (Universitas Pendidikan Indonesia (UPI), 2021)
WHO categorizes Covid-19 as a pandemic that has an impact on various aspects of life. In this condition, it turns out that there are still individuals who care to help others, one of which is the FPIPS Academic Society. Therefore, researchers are interested in raising this issue to be a study that aims to describe in-depth the actualization of the FPIPS Academic Society's caring character in responding to the pandemic based on moral knowing, moral feeling/attitude, and moral activity. This research study used a qualitative approach with the case study method. While the data collection techniques through observation, documentation study, and interviews online to selected participants based on snowball sampling technique. The general result is the actualization of social care characters FPIPS Academic Society's involve three-component characters, is knowing the good, desiring the good, and activity the good. The specific result of this research such as First, the academic community has good knowledge of social care by having knowing the moral values of social responsibility, awareness the factual issue related to Covid-19 and their impacts, have moral awareness, and moral reasoning so that they deciding social care is necessary for responding to the Covid-19 pandemic. Besides, they able to analyze, evaluate, and even contribute an idea related to social care. Second, the academic community shows a good sense of social care with a sense of empathy, a feeling of happiness to help, a feeling of confidence to help, and a growing desire to continue taking social care activities. The last, the social care actions practiced by the academic community are very diverse, both in light and weight scales, which can generally be classified as four classes, that is sharing, donating, cooperative, and donating.